2019
DOI: 10.3390/cancers11020202
|View full text |Cite
|
Sign up to set email alerts
|

SYK Inhibition Potentiates the Effect of Chemotherapeutic Drugs on Neuroblastoma Cells In Vitro

Abstract: Neuroblastoma is a malignancy arising from the developing sympathetic nervous system and the most common and deadly cancer of infancy. New therapies are needed to improve the prognosis for high-risk patients and to reduce toxicity and late effects. Spleen tyrosine kinase (SYK) has previously been identified as a promising drug target in various inflammatory diseases and cancers but has so far not been extensively studied as a potential therapeutic target in neuroblastoma. In this study, we observed elevated SY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 83 publications
0
6
1
1
Order By: Relevance
“…The signaling pathways by which Syk exerts its anti-proliferative and anti-invasive effects in epithelial cells remain unknown, and undoubtedly differ from the ones in hematopoietic cells where Syk appears to be pro-proliferative and pro-survival [29]. It is crucial to understand the mechanisms underlying this dual role because Syk kinase inhibitors might potentiate the effect of certain chemotherapeutic drugs in vitro [30] and they are being clinically evaluated but "their use might be inappropriate for people with a family history of breast cancer" [31]. Using a quantitative SILAC-based phosphoproteomic approach to compare mammary cell lines with different Syk expression or catalytic activity [32] we identified potential Syk substrate proteins involved in cell-cell adhesion (E-Cdh, α-Ctn) and epithelial polarity (occludin, Scrib, Dlg, ZO3, claudin3, InaDL, MAGUK5, and Lin7C).…”
Section: Introductionmentioning
confidence: 99%
“…The signaling pathways by which Syk exerts its anti-proliferative and anti-invasive effects in epithelial cells remain unknown, and undoubtedly differ from the ones in hematopoietic cells where Syk appears to be pro-proliferative and pro-survival [29]. It is crucial to understand the mechanisms underlying this dual role because Syk kinase inhibitors might potentiate the effect of certain chemotherapeutic drugs in vitro [30] and they are being clinically evaluated but "their use might be inappropriate for people with a family history of breast cancer" [31]. Using a quantitative SILAC-based phosphoproteomic approach to compare mammary cell lines with different Syk expression or catalytic activity [32] we identified potential Syk substrate proteins involved in cell-cell adhesion (E-Cdh, α-Ctn) and epithelial polarity (occludin, Scrib, Dlg, ZO3, claudin3, InaDL, MAGUK5, and Lin7C).…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence microscopy revealed the presence of SYK+ cells in the tissue sections of both MYCN-A and MYCN-NA NB human specimens and immunoreactivity of SYK in CD68+ TAMs ( Figure 2A ). A recent study has shown that Syk is abundantly present in both MYCN-A and MYCN-NA human NB tumors, but it is expressed explicitly in human MYCN-NA NB cell lines ( 40 ). Hence, we evaluated the protein expression of Syk in MYCN-A (SKNBE2, IMR 32) and MYCN-NA (SH-SY-5Y, SKNSH) human NB cell lines and immune cells isolated from the mice bearing NB9464 (MYCN-A) tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Recent emerging studies have shown that Syk also contributes to tumorigenesis; however, its role in the progression of solid tumors is complex ( 37 39 ). A recent report has shown that Syk acts as a tumor promoter in neuroblastoma and Syk inhibitors potentiate the effect of chemotherapeutic drugs on NB cells in vitro ( 40 ). However, this study did not reveal the presence of Syk in immune cells and the efficacy of Syk inhibitors in suppressing NB growth in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…DNA was eluted in 50 µL, and 5 µL was used in PCR. To test DNA quality, APRT PCR was carried out as previously described [ 42 ].…”
Section: Methodsmentioning
confidence: 99%